Standard specification for Steel Wire, Chromium-Silicon Alloy (American Society for Testing and Materials, 2003)
This specification covers round chromium-silicon alloy steel spring wire having properties and quality intended for the manufacture of springs resistant to set when used at moderately elevated temperatures. This product is not meant to be used for high cycle fatique applications (see Specification A877/A877M). This wire shall be provided either in the annealed and cold-drawn or oil-tempered condition as specified by the purchaser.